Malaria risk mapping in the Sahel Region of Nigeria: A geospatial approach - Mohammed Baba-Adamu; Modibbo Babagana-Kyari; Mohammed Bukar Ngamdu; Usman Adamu; Ahmed Abubakar Jajere (Sustinere: Journal of Environment and Sustainability)
Malaria remains a major public health challenge in Yobe State, Nigeria, with transmission patterns influenced by climatic, socio-economic and environmental factors. Understanding the spatial and temporal dynamics of malaria prevalence is crucial for effective intervention and policy planning. This study examined the trends, seasonality, and spatial variations in malaria prevalence across different ecological zones in Yobe State, providing insights into the impact of climate variability and other risk factors on malaria transmission. A geospatial approach was employed, utilizing malaria incidence data from Yobe State Government’s Epidemic Data Repository and health facilities across three ecological zones: the Sudan Savanna Zone (SuSZ), the Sahel Savanna Zone (SaSZ), and the Transition Zone (TZ). Temporal trends were analyzed using regression models, while spatial patterns were examined through hotspot analysis to identify high-burden areas. Findings revealed significant spatial and temporal variations in malaria prevalence. While malaria incidence showed no strong temporal trend in SaSZ (R² = 0.06) and TZ (R² = 0.04), Sudan Savanna Zone exhibited a notable increasing trend (R² = 0.77), suggesting a worsening malaria burden. Seasonal peaks in malaria cases aligned with the rainy season, emphasizing the role of climate in transmission. Spatial analysis identified persistent malaria hotspots in urban centers such as Gashua, Damaturu and Fika, where high population density and environmental factors contribute to transmission. These results underscore the need for climate-informed malaria control strategies, including enhanced surveillance, early warning systems, and targeted interventions in high-risk areas. Sustainable malaria control efforts must integrate climate predictions, improved healthcare access, and promote community engagement to prevent periodic resurgence and ensure long-term elimination goals are met.